Onchocerciasis transmission in Ghana: the human blood index of sibling species of the Simulium damnosum complex. Issue 1 (December 2016) - Lamberton, Poppy; Cheke, Robert; Walker, Martin; Winskill, Peter; Crainey, J.; Boakye, Daniel; Osei-Atweneboana, Mike; Tirados, Iñaki; Wilson, Michael; Tetteh-Kumah, Anthony; Otoo, Sampson; Post, Rory; et al.
Abstract Background Vector-biting behaviour is important for vector-borne disease (VBD) epidemiology. The proportion of blood meals taken on humans (the human blood index, HBI), is a component of the biting rate per vector on humans in VBD transmission models. Humans are the definitive host ofOnchocerca volvulus, but the simuliid vectors feed on a range of animals and HBI is a key indicator of the potential for human onchocerciasis transmission. Ghana has a diversity ofSimulium damnosum complex members, which are likely to vary in their HBIs, an important consideration for parameterization of onchocerciasis control and elimination models. Methods Host-seeking and ovipositing S. damnosum (sensu lato ) (s.l. ) were collected from seven villages in four Ghanaian regions. Taxa were morphologically and molecularly identified. Blood meals from individually stored blackfly abdomens were used for DNA profiling, to identify previous host choice. Household, domestic animal, wild mammal and bird surveys were performed to estimate the density and diversity of potential blood hosts of blackflies. Results A total of 11, 107 abdomens of simuliid females (which would have obtained blood meal(s) previously) were tested, with blood meals successfully amplified in 3, 772 (34 %). A single-host species was identified in 2, 857 (75.7 %) of the blood meals, of which 2, 162 (75.7 %) were human.Simulium soubrense Beffa form, S. squamosum C andS. sanctipauli Pra form were the most anthropophagic (HBI = 0.92, 0.86 and 0.70, respectively);S. squamosum E, S. yahense and S. damnosum (sensu stricto ) (s.s. )/S. sirbanum were the most zoophagic (HBI = 0.44, 0.53 and 0.63, respectively). The degree of anthropophagy decreased (but not statistically significantly) with increasing ratio of non-human/human blood hosts. Vector to human ratios ranged from 139 to 1, 198 blackflies/person. Conclusions DNA profiling can successfully identify blood meals from host-seeking and ovipositing blackflies. Host choice varies according to sibling species, season and capture site/method. There was no evidence that HBI is vector and/or host density dependent. Transmission breakpoints will vary among locations due to differing cytospecies compositions and vector abundances.